(untitled) (Proceedings of the Global Public Health Conference, 2025)
Ambient air pollution is a global threat in the 21st century, and its relationship to human health has been the focus of increasing research. The effects on development of Alzheimer’s disease and cognitive impairment, however, have not been extensively researched. Information is sparse on whether there is an association and what exactly the mechanism of insult might be. Meanwhile, global life expectancy and the incidence of Alzheimer’s disease as a cause of elderly dementia are on the rise. This study aims to explore the association between Alzheimer’s disease and chronic exposure to ambient air pollution. PubMed and Embase were queried with the following string: Air AND (pollution OR PM2.5 OR PM10 OR NO2 OR SO2 OR carbon monoxide OR ozone) AND (Alzheimer OR dementia OR cognition OR cognitive decline) for papers published between 2020 and 2024. 36 articles meeting review criteria were found, and 8 articles were selected for contextual information. The simple answer was yes; ambient air pollution, most often PM2.5, appears to increase the risk for dementia and cognitive decline. Insights into mechanisms were also found, including direct deposition of particles and cortical atrophy. There is even some evidence that the damage is attenuable. However, the study has limitations as there has been no statistical analysis of the studies presented, and the search criteria were not created in accordance with any standard. As countries tend toward clean air, further research into the prevention of air pollution related cognitive impairment is warranted. The greatest gap in research is in prevention, though one study herein suggests a strong policy enforced by governments may help prevent excess cases of Alzheimer’s disease due to air pollution.